Evaluasi Kinerja Laboratorium Pengujian Bahan Konstruksi dalam Penerapan ISO/IEC 17025:2017 (Studi Kasus: UPTD.LBK DINAS PUPR PROV.SUMUT) - Azhari, Firdha Aulia Ariyani; Anas, M. Ridwan; Tarigan , Ahmad Perwira Mulia (Syntax Literate, 2026)
Construction materials testing laboratories play a strategic role in ensuring the quality of infrastructure development. The implementation of ISO/IEC 17025:2017 as a quality management system is a crucial instrument to guarantee technical competence and the validity of test results. However, the effectiveness of this standard's implementation in achieving strategic performance in government laboratories remains underexplored. This study was conducted at the Construction Materials Laboratory Unit (UPTD) of the Department of Public Works and Spatial Planning (PUPR), North Sumatra Province, with the objective of evaluating laboratory performance through the integration of ISO/IEC 17025:2017 and the Balanced Scorecard (BSC) approach. A mixed methods design was employed with purposive sampling involving 60 respondents—30 internal personnel and 30 external service users. Data were collected through questionnaires, structured interviews, and document-based observations. Multiple linear regression analysis of 16 ISO-related variables identified three significant predictors of performance: Traceability Investment (β=0.044), Method Validity (β=0.023), and Management Transparency (β=0.030). Four additional variables with strong beta coefficients derived from interviews and observations were also considered in defining strategic objectives. The BSC-based performance evaluation yielded an overall score of 77.35% ("fairly good"), with the highest contributions from the customer and financial perspectives. The resulting evaluation model offers a practical reference for strengthening accountable and sustainable governance in public laboratories. Future research is recommended to apply this model to government laboratories of varying scale, complexity, and organizational structure in order to assess its external validity and contextual adaptability.